2009
DOI: 10.1007/s10334-009-0183-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cardiac motion on diffusion-weighted magnetic resonance imaging of the liver

Abstract: Purpose To assess cardiac motion-induced signal loss in diffusion-weighted magnetic resonance imaging (DWI) of the liver using dynamic DWI. Materials and methods Three volunteers underwent dynamic coronal DWI of the liver under breathholding, in the diastolic (DWI diast ) or systolic (DWI syst ) cardiac phase, and with motion probing gradients (MPGs) in phase encoding (P, left-right), frequency encoding (M, superior-inferior), or slice select (S, anterior-posterior) direction. Liver-to-background contrasts (LB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 14 publications
7
101
1
Order By: Relevance
“…In addition, some ROIs were chosen in the left liver lobe. Lesions located in the left lobe, especially close to the edge of the liver, are susceptible to be affected by cardiac or diaphragm motion and gastrointestinal peristalsis (47)(48)(49). It is recommended to select lesions located in the center of the right liver lobe because it is more stable and leads to less overestimation during measurements (50); adding echocardiography triggering could decrease parametric variability effectively (49).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some ROIs were chosen in the left liver lobe. Lesions located in the left lobe, especially close to the edge of the liver, are susceptible to be affected by cardiac or diaphragm motion and gastrointestinal peristalsis (47)(48)(49). It is recommended to select lesions located in the center of the right liver lobe because it is more stable and leads to less overestimation during measurements (50); adding echocardiography triggering could decrease parametric variability effectively (49).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of DWI is that the evaluation of structures close to the heart, such as mediastinal lymph nodes and the left liver lobe, may be compromised because of signal loss and artifacts due to severe tissue motion (33,(44)(45)(46). Nevertheless, MRI is a versatile imaging modality, and the addition of other sequences may improve the evaluation of the mediastinal lymph nodes (24,47) (Fig.…”
Section: Limitationsmentioning
confidence: 99%
“…Thus, the ADC measurements in the right liver lobe may be lower than in the left lobe, because of the addition of heart motion (17). Other authors have shown that cardiac motion may affect the signal intensity of both the left and right lobes (18), which may explain why the differences between the two lobes were of no importance in our study. As demonstrated in our study, an interobserver variability also exists.…”
Section: Discussionmentioning
confidence: 64%